2016
DOI: 10.3389/fpubh.2016.00234
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nasal Colonization by Methicillin-Resistant Staphylococcus aureus in Persons Using a Homeless Shelter in Kansas City

Abstract: Nasal colonization of methicillin-resistant Staphylococcus aureus (MRSA) plays an important role in the epidemiology and pathogenesis of disease. Situations of close-quarter contact in groups are generally regarded as a risk factor for community-acquired MRSA strains due to transmission via fomites and person-to-person contact. With these criteria for risk, homeless individuals using shelter facilities, including showers and toilets, should be considered high risk for colonization and infection. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In agreement with this, a study conducted between July 2012-June 2014 on a homeless shelter in Kansas City showed that individuals in this homeless shelter are at high risk of obtaining an MRSA infection. In addition, the risk of infections within such individuals was significantly higher than the general population with a prevalence of 9.8% in homeless groups compared to 1.8% in the general population [97]. Another study conducted in April, 2006 in Canada revealed a 4.5% prevalence of MRSA colonization among residents of three homeless shelters in Ottawa, Ontario [98].…”
Section: Homeless Sheltersmentioning
confidence: 98%
See 1 more Smart Citation
“…In agreement with this, a study conducted between July 2012-June 2014 on a homeless shelter in Kansas City showed that individuals in this homeless shelter are at high risk of obtaining an MRSA infection. In addition, the risk of infections within such individuals was significantly higher than the general population with a prevalence of 9.8% in homeless groups compared to 1.8% in the general population [97]. Another study conducted in April, 2006 in Canada revealed a 4.5% prevalence of MRSA colonization among residents of three homeless shelters in Ottawa, Ontario [98].…”
Section: Homeless Sheltersmentioning
confidence: 98%
“…Closed community settings are considered areas of high-risk for CA-MRSA transmission, colonization, and infection due to increased person-to-person contact [97]. Homeless shelters are a very good example of such high-risk community settings.…”
Section: Homeless Sheltersmentioning
confidence: 99%
“…In healthy subjects, over time, three patterns of carriage can be distinguished: about 20% of people are persistent carriers, 60% are intermittent carriers, and approximately 20% almost never carry S. aureus. Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of S. aureus identified for the first time in the United Kingdom in 1961, which is resistant to β-lactam antibiotics [4,5]. Initially, these bacteria were considered a concern for hospitalized patients until in the last two decades strains of MRSA have emerged in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are available regarding the prevalence of antimicrobial resistance in homeless populations. An 8–10% prevalence of methicillin-resistant Staphylococcus aureus was evidenced in nasal sample from homeless people in Kansas City and in Boston, USA with resistance to erythromycin, levofloxacin and clindamycin 3,4. A study conducted in New Orleans, USA evidenced that housing in homeless shelter was an independent risk factor for high level of penicillin-non-susceptible Streptococcus pneumoniae carriage 5…”
Section: Introductionmentioning
confidence: 99%